Utilization of Euphorbia nivuliafor Biogas Production - Shilpkar, Prateek; Shah, Mayur; Acharya, Pradip (Asian Journal of Chemistry, 2010)
Thor (Euphorbia nivulia) plant was co-digested with buffalo dung at 6 % total solids for biogas production in laboratory scale experiment on daily feeding basis. The experiment was run for a total of 120 d and data regarding quality as well as quality of biogas and fertilizer value of biogas slurry were recorded. Results show that co-digestion of thor with buffalo dung gives 101.36 per cent increased biogas production with methane content of 66.84 per cent. Biogas slurry from codigestion also contains 55.36, 0.69 and 3682.35 % higher nitrogen, phosphorous and potassium compared to that of buffalo dung alone.